Constitutional Religious Tolerance in Realizing the Protection of Human Rights in Indonesia - Nurfaika Ishak; Romalina Ranaivo Mikea Manitra (Journal of Human Rights, Culture and Legal System, 2022)
Tolerance in the dynamic of Indonesian society and socio-cultural diversity is necessary. It is crucial to examine constitutional regulations as the highest fundamental law. The government has issued various regulations, but the critical question is whether these regulations protect religious freedom. This study aims to figure out how the law of religious tolerance ruled in the Constitution of the Republic of Indonesia/ Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. This research is a type of normative research by describing, analyzing, and describing the constitutional arrangement of religious tolerance as a form of protection of human rights in Indonesia. The approach used is legal by tracing all relevant laws and regulations. The data collection technique used in this study is a library research technique, which is a data collection technique by reviewing journals, rules, regulations, and other related materials related to the law of religious tolerance in Indonesia. The results showed that religious tolerance is a form of protection for human rights recognized in Indonesia as a country with diversity. Tolerance is one of the keys to religious harmony based on mutual understanding and respect as human beings.